2016
DOI: 10.1039/c5sc04383b
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale imaging of anticancer platinum(iv) compounds in murine tumor and kidney

Abstract: A NanoSIMS, LA-ICP-MS and TEM combinatorial approach was applied to analyze the distribution of platinum(iv) prodrugs in murine tissue samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 65 publications
2
33
0
Order By: Relevance
“…NanoSIMS allows high spatial resolution imaging (B100 nm) of the metal centre and when used in tandem with isotopic labelling, provides valuable information on the ligands surrounding the metal centre. 17,18 In recent years, NanoSIMS has been used to study cellular distribution of metallodrugs based on Au, 19 Ru 17 and Pt, [20][21][22] with the cellular distribution of cisplatin being reported in colon cancer cells. Despite the high spatial resolutions of this technique, as far as we are aware no comparative study has been done to analyse with high spatial resolution differences in the distribution of Pt between cancer cells that are sensitive and resistant to the drug.…”
Section: Introductionmentioning
confidence: 99%
“…NanoSIMS allows high spatial resolution imaging (B100 nm) of the metal centre and when used in tandem with isotopic labelling, provides valuable information on the ligands surrounding the metal centre. 17,18 In recent years, NanoSIMS has been used to study cellular distribution of metallodrugs based on Au, 19 Ru 17 and Pt, [20][21][22] with the cellular distribution of cisplatin being reported in colon cancer cells. Despite the high spatial resolutions of this technique, as far as we are aware no comparative study has been done to analyse with high spatial resolution differences in the distribution of Pt between cancer cells that are sensitive and resistant to the drug.…”
Section: Introductionmentioning
confidence: 99%
“…31 P is typically most abundant in the nucleus, which can be further segmented into the 32 Sintense nucleolus and 32 S-sparse nucleoplasm. Within the cytoplasm, 32 S is enriched in some (but not all) lysosomes, providing some definition for intracellular vesicles (Legin et al, 2014(Legin et al, , 2016Narendra et al, 2020). Additionally, in some tissues, such as the heart…”
Section: Narendra and Steinhausermentioning
confidence: 99%
“…[301] Recently, the use of nanoscale secondary ion mass spectrometry (nanoSIMS), which consists in a nanoscopic scale resolution imaging technique, was reported to localise Au-and Pt-based metallodrugs in tumors. [302,303] Keppler et al first reported the use of a combined LA-ICP-MS and nanoSIMS approach in complex biological systems (kidney and tumour samples) after treatment with Pt(IV) pro-drugs. [303] The results revealed that uneven platinum distribution was occurring in both the organ and subcellular fractions.…”
Section: Ms Analyses Of Metallodrugs In Complex Biological Systemsmentioning
confidence: 99%
“…[302,303] Keppler et al first reported the use of a combined LA-ICP-MS and nanoSIMS approach in complex biological systems (kidney and tumour samples) after treatment with Pt(IV) pro-drugs. [303] The results revealed that uneven platinum distribution was occurring in both the organ and subcellular fractions.…”
Section: Ms Analyses Of Metallodrugs In Complex Biological Systemsmentioning
confidence: 99%
See 1 more Smart Citation